From Home to Abroad: The Intergenerational Impact of Household Member Migration on Women’s Economic & Social Empowerment in Egypt - Elgohary, Menna (AUC Knowledge Fountain, 2025)
This thesis investigates to what extent the migration of a household member to an Arab country leads to increased social and economic empowerment among Egyptian women of two age categories (15-35 and +35) over two waves. Determined through Principle Component Analysis (PCA) of panel data from Egypt Labor Market Panel Surveys in 2018 and 2023, composite indices of social and economic empowerment serve as dependent variables in an IV 2SLS regression model. The model assesses whether household member migration, proxied by migration prevalence on the district (qism) level as an IV, causes a significant increase in social and economic empowerment among Egyptian women while accounting for factors such as marital status, education, and household characteristics. The findings showcase that household migration to Arab countries decreases economic empowerment for Egyptian women, with significant impacts on younger women over both waves. Social empowerment is also affected by migration in which younger women experience increased empowerment in 2018 but declines in 2023, while older women face negative impacts in both years, specifically in mobility and autonomy.